Ultra-broadband Polarization Insensitive Optical Power Splitter based on Si3N4 Waveguide - XIE Yating; HONG Yihan; ZHANG Yi; ZENG Zhihong; LU Yimin (Guangtongxin yanjiu, 2024)
【Objective】In order to solve the problem of the limited bandwidth of polarization insensitive optical power splitter, an ultra-broadband polarization insensitive optical power splitter based on Silicon Nitride (Si3N4) waveguide is proposed.【Methods】The ultra-broadband polarization insensitive optical power splitter is designed based on adiabatic coupling Si3N4 waveguide.Optical bandwidth of 300 nm (from 1 400 ~ 1 700 nm) is demonstrated for both Transverse Electric (TE) and Transverse Magnetic (TM) modes.【Results】Over the entire optical bandwidth, the losses for TE and TM mode are less than 0.10 and 0.15 dB, respectively.The footprint of the proposed ultra-broadband polarization insensitive optical power splitter is only 60.00 μm×2.75 μm, which means that the optical power splitter can be used for large-scale integration.Furthermore, the relationship between the performance and the structure parameters of the proposed optical power splitter is studied.【Conclusions】The results show that the performance of the optical power splitter maintains almost unchanged by varying the structure parameters with ±50 nm.In other words, the optical power splitter possesses large fabrication tolerance which can be easily fabricated.